Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
Ta có : \(\frac{a^2+b^2}{c^2+d^2}=\frac{ab}{cd}\)
\(\Leftrightarrow\left(a^2+b^2\right)cd=ab\left(c^2+d^2\right)\)
\(\Leftrightarrow a^2cd+b^2cd=abc^2+abd^2\)
\(\Leftrightarrow\left(a^2cd-abd^2\right)+\left(b^2cd-abc^2\right)=0\)
\(\Leftrightarrow ad\left(ac-bd\right)-bc\left(ac-bd\right)=0\)
\(\Leftrightarrow\left(ac-bd\right)\left(ad-bc\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}ac=bd\\ad=bc\end{cases}}\)
\(\Leftrightarrow\orbr{\begin{cases}\frac{a}{b}=\frac{c}{d}\\\frac{a}{b}=\frac{d}{c}\end{cases}}\) (đpcm)
![](https://rs.olm.vn/images/avt/0.png?1311)
Đặt \(\frac{a}{b}=\frac{c}{d}=k\) ,ta có:
\(a=bk,c=dk\)
\(\Rightarrow\frac{\left(a+b\right)^2}{\left(c+d\right)^2}=\frac{\left(bk+b\right)^2}{\left(dk+d\right)^2}=\frac{\left[b.\left(k+1\right)\right]^2}{\left[d.\left(k+1\right)\right]^2}=\frac{b^2.\left(k+1\right)^2}{d^2.\left(k+1\right)^2}=\frac{b^2}{d^2}\)(1)
\(\frac{ab}{cd}=\frac{bkb}{dkd}=\frac{b^2}{d^2}\)(2)
Từ (1) và (2) suy ra:
\(\frac{\left(a+b\right)^2}{\left(c+d\right)^2}=\frac{ab}{cd}\)(đpcm)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\frac{a}{b}=\frac{b}{c}\)\(\Rightarrow\left(\frac{a}{b}\right)^2=\left(\frac{b}{c}\right)^2=\frac{a^2}{b^2}=\frac{b^2}{c^2}=\frac{a^2+b^2}{b^2+c^2}\)
mà \(\left(\frac{a}{b}\right)^2=\frac{a}{b}.\frac{a}{b}=\frac{a}{b}.\frac{b}{c}=\frac{a}{c}\)
\(\Rightarrow\frac{a^2+b^2}{b^2+c^2}=\frac{a}{c}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\frac{a^2+c^2}{a^2+b^2}=\frac{c}{b}\Leftrightarrow b\left(a^2+c^2\right)=c\left(a^2+b^2\right)\Leftrightarrow a^2b+bc^2=a^2c+b^2c\)
\(\Leftrightarrow a^2b-a^2c=b^2c-bc^2\Leftrightarrow a^2\left(b-c\right)=bc\left(b-c\right)\Leftrightarrow a^2=bc\Leftrightarrow\frac{a}{b}=\frac{c}{a}\)(đpcm)
![](https://rs.olm.vn/images/avt/0.png?1311)
Ta có : \(\frac{1}{c}=\frac{1}{2}\left(\frac{1}{a}+\frac{1}{b}\right)\)
\(\Leftrightarrow\frac{1}{c}=\frac{a+b}{2ab}\)
\(\Leftrightarrow ca+cb=2ab\)
\(\Leftrightarrow ac-ab=ab-bc\)
\(\Leftrightarrow a\left(c-b\right)=b\left(a-c\right)\)
\(\Leftrightarrow\frac{a}{b}=\frac{a-c}{c-b}\left(đpcm\right)\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\frac{a}{b}=\frac{b}{c}\Rightarrow\frac{a}{b}.\frac{b}{c}=\frac{a}{b}.\frac{a}{b}=\frac{b}{c}.\frac{b}{c}\Rightarrow\frac{a}{c}=\frac{a^2}{b^2}=\frac{b^2}{c^2}=\frac{a^2+b^2}{b^2+c^2}\)
\(\Leftrightarrow\frac{a^2}{b^2}=\frac{b^2}{c^2}=\frac{a}{b}.\frac{b}{c}=\frac{a}{c}=\frac{a^2+b^2}{b^2+c^2}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
Từ \(gt\Leftrightarrow\frac{1}{c}=\frac{1}{2}.\frac{a+b}{ab}\)
\(\Leftrightarrow\frac{1}{c}=\frac{a+b}{2ab}\Leftrightarrow c\left(a+b\right)=2ab\Leftrightarrow ac+bc=ab+ab\)
\(\Leftrightarrow ac-ab=ab-bc\Leftrightarrow a\left(c-b\right)=b\left(a-c\right)\)
\(\Rightarrow\frac{a}{b}=\frac{a-c}{b-c}\) (đpcm)
Từ \(gt\Leftrightarrow\frac{1}{c}=\frac{1}{2}.\frac{a+b}{ab}\)
\(\Leftrightarrow\frac{1}{c}=\frac{a+b}{2ab}\Leftrightarrow c\left(a+b\right)=2ab\Leftrightarrow ac+bc=ab+ab\)
\(\Leftrightarrow ac-ab=ab-bc\Leftrightarrow a\left(c-b\right)=b\left(a-c\right)\)
\(\Rightarrow\frac{a}{b}=\frac{a-c}{b-c}\)
\(\Rightarrowđpcm\)
http://123link.pro/O3IFQ5dc